Evidence for B cell maturation but not trained immunity in uninfected infants exposed to hepatitis C virus. Issue 12 (27th April 2020) - Lutckii, Anton; Strunz, Benedikt; Zhirkov, Anton; Filipovich, Olga; Rukoiatkina, Elena; Gusev, Denis; Lobzin, Yuriy; Fischler, Björn; Aleman, Soo; Sällberg, Matti; Björkström, Niklas K
Abstract : Objectives: Vertical transmission of hepatitis C virus (HCV) is rare compared with other chronic viral infections, despite that newborns have an immature, and possibly more susceptible, immune system. It further remains unclear to what extent prenatal and perinatal exposure to HCV affects immune system development in neonates. Design: To address this, we studied B cells, innate immune cells and soluble factors in a cohort of 62 children that were either unexposed, exposed uninfected or infected with HCV. Forty of these infants were followed longitudinally from birth up until 18 months of age. Results: As expected, evidence for B cell maturation was observed with increased age in children, whereas few age-related changes were noticed among innate immune cells. HCV-infected children had a high frequency of HCV-specific IgG-secreting B cells. Such a response was also detected in some exposed but uninfected children but not in uninfected controls. Consistent with this, both HCV-exposed uninfected and HCV-infected infants had evidence of early B cell immune maturation with an increased proportion of IgA-positive plasma cells and upregulated CD40 expression. In contrast, actual HCV viraemia, but not mere exposure, led to alterations within myeloid immune cell populations, natural killer (NK) cells and a distinct soluble factor profile with increased levels of inflammatory cytokines and chemokines. Conclusion: Our data reveal that exposure to, and infection with, HCV causes disparate effects on adaptive B cells and innate immune cell such as myeloid cells and NK cells in infants.